Pengaruh Media Promosi Perbankan Syariah Terhadap Minat Menabung Masyarakat Gang Pos Di Bank Syariah - Fajar, Ade; Salama, Hartini; Sari, Shania Ratna (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This study aims to determine the promotion media of sharia banking that influence the public interest to save in sharia banks, Promotion media used by sharia banking in this research are divided into 3, namely newspaper media, television media and internet media. The method used in this research was quantitative descriptive method with multiple linier regression analysis technique. The data used in this research is the primary data in the form of questionnaires distributed to the public. Based on the data analysis that has been done, the television and internet variables have a greater contribution than the newspaper variable in increasing public interest in saving at the Islamic banks.